Foliar Nutrient Concentrations of European Beech in Switzerland: Relations With Nitrogen Deposition, Ozone, Climate and Soil Chemistry - Braun, Sabine; Schindler, Christian; Rihm, Beat (Frontiers in Forests and Global Change, 2020)
Excess deposition of the mineral nutrient nitrogen (N) is a serious threat for European forests. Its effect on foliar nutrient concentrations of Fagus sylvatica, along with other predictors, was analyzed in the present study which bases on 30 year's observation data in 74 forest monitoring plots in Switzerland. The data include gradients in soil chemistry, climate, nitrogen (N) deposition and ozone concentration. This long-term forest monitoring study shows that foliar concentrations of phosphorus (P), magnesium (Mg) and potassium (K) decreased over time. Current foliar P concentrations indicate acute P deficiency, assessed both from the concentration and the N:P ratio thresholds. In addition, also the relation between N deposition and foliar concentrations of N and P changed over time. Initially, the N concentrations were positively and the P concentrations not correlated with N deposition. Today, N concentrations are negatively and P strongly negatively related, suggesting a progressive N saturation. Interactions between N deposition and soil chemistry suggest an impaired uptake of K and P at higher N loads. The decline of foliar Mg concentrations seems to be a result of soil acidification mediated by N deposition. Additionally, ozone impaired foliar P uptake. We could observe an increase in leaf weight over time while there was no time trend in P and K mass per leaf. This could be interpreted as a dilution effect but detailed regression analysis argues against the dilution hypothesis. Overall, the changing relation between N deposition and foliar N and P support the nitrogen saturation hypothesis.